Identification of ibuprofen targeting CXCR family members to alleviate metabolic disturbance in lipodystrophy based on bioinformatics and in vivo experimental verification - Cao, Zhiwen; Zhao, Yuxiao; Liu, Ruixin; Yan, Xialin; Wang, Jiqiu; Chen, Na (Frontiers in Endocrinology, 2024)
Background: Lipodystrophy is a rare disease that is poorly diagnosed due to its low prevalence and frequent phenotypic heterogeneity. The main therapeutic measures for patients with clinical lipodystrophy are aimed at improving general metabolic complications such as diabetes mellitus, insulin resistance, and hypertriglyceridemia. Therefore, there is an urgent need to find new biomarkers to aid in the diagnosis and targeted treatment of CGL patients.Methods: Dataset GSE159337 was gained via Gene Expression Omnibus database. First, differentially expressed genes between congenital generalized lipodystrophy and control samples were yielded via differential expression analysis and were analyzed for Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment to explore the functional pathways. Next, the protein-protein interaction analysis and MCC algorithm were implemented to yield candidate genes, which were then subjected to receiver operating characteristic analysis to identify biomarkers with an area under the curve value exceeding 0.8. Moreover, random forest, logistic regression, and support vector machine analyses were carried out to assess the diagnostic ability of biomarkers for CGL. Finally, the small molecule drugs targeting biomarkers were predicted and ibuprofen was further validated in lipodystrophy mice.Results: Totally 71 DEGs in GSE159337 were sifted out, and were involved in immune receptor activity, immune response-regulating signaling pathway and secretory granule membrane. Besides, the CXCR2, TNFSF10, NLRC4, CCR2, CEACAM3, TLR10, TNFAIP3, and JUN were considered as biomarkers by performing ROC analysis on ten candidate genes. Meanwhile, the RF, logistic regression and SVM analyses further described those biomarkers had an excellent diagnosis capability for CGL. Eventually, the drug-gene network included ibuprofen-CXCR1, ibuprofen-CXCR2, Cenicriviroc-CCR2, Fenofibrate-JUN and other relationship pairs. Ibuprofen treatment was also validated to downregulate CXCR1 and CXCR2 in PBMC and improve glucose tolerance, hypertriglyceridemia, hepatic steatosis and liver inflammation in lipodystrophy mice.The eight biomarkers, namely CXCR2, TNFSF10, NLRC4, CCR2, CEACAM3, TLR10, TNFAIP3, and JUN were identified through bioinformatic analyses, and ibuprofen targeting CXCR1 and CXCR2 in PBMC was showed to improve metabolic disturbance in lipodystrophy, contributing to studies related to the diagnosis and treatment of lipodystrophy.